FISH AND DECAPODS IN THE ESTUARIES OF THE OLGA BAY - P. G. Milovankin (Известия ТИНРО)
Species composition in 64 catches obtained by fry seine (length 15 m, height 2.5 m, mesh size 5 mm) in the estuaries of the Olga Bay (Primorye) in the daytime in warm seasons of the 2012 and 2013 are analyzed, including 4 catches in the Olga River estuary, 43 in the Avvakumovkа estuary and 17 in the Tihaya Pristan Bight, as the common external estuary of both rivers. In total, 53 taxa of aquatic organisms belonged to 23 families were defined: 49 fish species and 4 species of decapods. The families with the highest species diversity were Cottidae — 7 species, Gobiidae — 5 species, and Hexagrammidae — 5 species. The most common species were Tribolodon spp. (occurrence 92 %), Crangon spp. (66 %), Gasterosteus nipponicus (64 %), and Megalocottus platycephalus taeniopterus (59 %). The species richness decreased in the order: Tihaya Pristan Bight (42 species) — Avvakumovka estuary (29 species) — Olga estuary (11 species). Seven mass species made about 90 % of the total catch: Tribolodon spp., Eriocheir japonica, Megalocottus platycephalus taeniopterus, Platichthys stellatus, Gasterosteus nipponicus, Oncorhynchus keta, and Hypomesus sp. Among them, M. platycephalus taeniopterus and Tribolodon spp. were the most frequent. Species domination by Simpson index decreased in the order: Olga estuary (0.434) — Tihaya Pristan Bight (0.373) — Avvakumovka estuary (0.243). The biomass distribution density was calculated using the coefficient of catchability 1.0. It was the highest in the Tihaya Pristan Bight — 10.1 g/m2 and considerably lower in both internal estuaries: the Avvakumovka — 6.1 g/m2 and the Olga — 4.9 g/m2. The mean density fluctuated in the range of 2.5–8.9 g/m2 with the average value of 6.7 g/m2. Tribolodon spp., E. japonica, P. stellatus, M. platycephalus taeniopterus, and G. nipponicus prevailed in the freshwater biotopes of the internal estuaries distinguished by low salinity and strong water flow with the mean distribution density 2.5, 0.9, 0.7, 0.6, and 0.4 g/m2, respectively. Tribolodon spp., M. platycephalus taeniopterus, H. octogrammus, M. stelleri, L. pinnifasciata, and O. ocellatus prevailed in the marine biotopes of the external estuary distinguished by relatively warm, salty and calm water, shallow depths and thickets of Zostera marina, their mean distribution density was 10.1, 2.7, 0.7, 0.5, 0.4, and 0.4 g/m2, respectively.